2007
DOI: 10.5395/jkacd.2007.32.2.095
|View full text |Cite
|
Sign up to set email alerts
|

Pulp response of mineral trioxide aggregate, calcium sulfate or calcium hydroxide

Abstract: This study was performed to verify the possibility of MTA and calcium sulfate as a pulp capping agent through comparing the dental pulp response in dogs after capping with MTA, calcium sulfate, and calcium hydroxide.24 teeth of 2 dogs, 8 month old, were used in this study. Under general anesthesia, cervical cavities were prepared and pulp was exposed with sterilized #2 round bur in a high speed handpiece.MTA, calcium hydroxide, and calcium sulfate were applied on the exposed pulp. Then the coronal openings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…[2][3][4] 1990년대부터 사용되기 시작한 mineral trioxide aggregate (MTA)를 치수복조술에 사용하려는 다양한 시 도가 진행되어 원숭이나 개의 치아에 MTA와 수산화칼슘을 이용한 치수복조술을 시행한 실험에서 MTA가 경조직 형성 에 더 좋은 결과를 보여 주었다. [5][6][7][8] 또 수산화칼슘을 사용한 경우보다 MTA가 치수의 integrity를 유지하는 면에 있어 서 우수한 것으로 보고되었으며 9 노출된 치수에 MTA를 적 용한 경우 더 많은 경조직이 형성되며 염증반응이 더 적게 발생하는 것으로 알려져 있다. 10,11 그러나 또 다른 연구들에 서는 수산화칼슘에 비하여 MTA를 적용한 경우 치수조직의 초기 치유가 빠르게 일어나는 현상을 제외하고 이후에 발생 하는 조직의 치유양상은 비슷하며 임상적인 결과도 큰 차이 가 없음을 보고 하였다.…”
Section: 서 론unclassified
“…[2][3][4] 1990년대부터 사용되기 시작한 mineral trioxide aggregate (MTA)를 치수복조술에 사용하려는 다양한 시 도가 진행되어 원숭이나 개의 치아에 MTA와 수산화칼슘을 이용한 치수복조술을 시행한 실험에서 MTA가 경조직 형성 에 더 좋은 결과를 보여 주었다. [5][6][7][8] 또 수산화칼슘을 사용한 경우보다 MTA가 치수의 integrity를 유지하는 면에 있어 서 우수한 것으로 보고되었으며 9 노출된 치수에 MTA를 적 용한 경우 더 많은 경조직이 형성되며 염증반응이 더 적게 발생하는 것으로 알려져 있다. 10,11 그러나 또 다른 연구들에 서는 수산화칼슘에 비하여 MTA를 적용한 경우 치수조직의 초기 치유가 빠르게 일어나는 현상을 제외하고 이후에 발생 하는 조직의 치유양상은 비슷하며 임상적인 결과도 큰 차이 가 없음을 보고 하였다.…”
Section: 서 론unclassified
“…그러나, 인간 치수세포의 분화에 대한 β -glycerophosphate와 dexamethasone의 적정 농도는 아 직 보고된 바가 없다. 직접 치수 복조에서 MTA가 수산화칼슘보다 더 생체 친 화적이며 6) , 세포 증식을 증가시키며 7) , 수중에서 장기간 용 해되면서 수산화칼슘을 방출하여 주변 조직의 석회화를 촉 진한다는 보고가 있다 8,9) . MTA의 주요 구성물은 Portland cement와 bismuth oxide이고 10) , bismuth oxide는 방사 선 불투과성을 증가시키기 위해 첨가된다.…”
unclassified
“…8 In animal studies, MTA proved to be more biocompatible to pulp tissue than calcium hydroxide and calcium sulfate as pulp capping material. 9 MTA was also the only material studied that allowed cementum overgrowth. 10,11 In vitro studies of human osteoblasts showed that MTA stimulated cytokine release and interleukin production.…”
Section: Introductionmentioning
confidence: 99%
“…3 The biocompatibility of MTA has been assessed in many studies. [3][4][5][6][7][8][9][10][11][12][13][14] Calcium hydroxide which is biocompatible with tissue, is the main compound released by MTA in water. 3 The results of an in vitro study showed that MTA was less toxic than amalgam, SuperEBA and IRM.…”
Section: Introductionmentioning
confidence: 99%